Product design: Nanoparticle‐Loaded polyvinyl butyral interlayer for solar control. Issue 10 (29th June 2018) - Ge, Shaqi; Wang, Neng; Fung, Ka Yip; Wong, Ka Wai; Chan, Che Ting; Ng, Ka Ming
Abstract : A systematic procedure for the design of nanoparticle‐loaded polyvinyl butyral (PVB) interlayer for solar control applications is developed. Desirable product attributes—transparency, energy savings, pleasant color, and so on and the related product specifications—transmittance of visible light, solar heat gain coefficient, color coordinates, and so on are met by properly selecting the type(s) of nanoparticles, their volume fraction in the PVB interlayer, and so on. The selection is based on the Maxwell Garnett relation to account for the localized surface plasmon resonance of the nanoparticles, Beer–Lambert's law, various international standards, and a database of transmittance and reflectance developed in our laboratory. The final product that meets all the product specifications as verified by prototypes is obtained by iterating between predictions and experiments. A causal table is provided to guide the verification step. Two examples of preparing solar control PVB interlayers with different specifications are provided to illustrate this design procedure. © 2018 American Institute of Chemical Engineers AIChE J, 64: 3614–3624, 2018